Motivation toward Physical Education and habitual physical activity in adolescents (Agora for Physical Education and Sport, 2020)
The aim of this study was to analyze the motivation towards Physical Education (PE) and regular physical activity focusing on gender and everyday physical activity practice. The study sample consisted of 83 students, aged between 14 and 17 years (M = 15.06; SD = .79), from a secondary education school in Valencia (Spain) The instruments used were the Motivation Questionnaire in the PE Classes (CMEF), which measures intrinsic motivation, identified regulation, introjected regulation, external regulation and amotivation, and the Inventory on Habitual Physical Activity in Adolescents (IHPAA), composed of physical sports activity, physical activity in the school environment and physical activity in leisure time. The results showed that boys have a greater intrinsic motivation and physical activity level than girls. Likewise, those students with a higher level of regular physical activity practice registered more intrinsic motivation and identified regulation towards PE, and lower amotivation.
Keywords: Physical Education; motivation; physical activity; adolescence; gender